High-sensitivity detection of chlorothalonil via terahertz metasensor - Yixing Zhang; Yunxia Ye; Xiaoxian Song; Maosheng Yang; Yunpeng Ren; Xudong Ren; Lanju Liang; Jianquan Yao (Materials Research Express, 2020)
Given the complex pretreatment and low sensitivity of pesticide residue detection with the conventional testing method, a Terahertz metasensor consisting of the four-division ring resonator (FSRRs) was proposed and fabricated for the identification and detection of chlorothalonil. Through simulations, the theoretical sensitivity of this metasensor was found to reach 156.3 GHz /RIU (RIU, refractive index unit) under an analyte layer 1 μ m thick. Through experiments, firstly, the characteristic fingerprint spectrum of chlorothalonil in the THz band was obtained by detecting solid chlorothalonil with THz time-domain spectrum system. Then, Terahertz metasensor was used to detect the chlorothalonil solutions of different concentrations. The experimental results showed that the resonant peak of the metasensor was redshifted with the increase of chlorothalonil concentration. Compared with the detection strategy only using the characteristic fingerprint spectrum, the sensitivity of the metasensor improved 106 times, which was up to a minimum of 1 mg l ^−1 . This study indicates that the metasensor is a promising optical device for detecting the pesticide residues with a very high sensitivity.